Unveiling acquired resistance to anti-EGFR therapies in colorectal cancer: a long and winding road - Ríos-Hoyo, Alejandro; Monzonís, Xavier; Vidal, Joana; Linares, Jenniffer; Montagut, Clara (Frontiers in Pharmacology, 2024)
Emergence of acquired resistance limits the efficacy of the anti-EGFR therapies cetuximab and panitumumab in metastatic colorectal cancer. In the last decade, preclinical and clinical cohort studies have uncovered genomic alterations that confer a selective advantage to tumor cells under EGFR blockade, mainly downstream re-activation of RAS-MEK signaling and mutations in the extracellular domain of EGFR (EGFR-ECD). Liquid biopsies (genotyping of ctDNA) have been established as an excellent tool to easily monitor the dynamics of genomic alterations resistance in the blood of patients and to select patients for rechallenge with anti-EGFR therapies. Accordingly, several clinical trials have shown clinical benefit of rechallenge with anti-EGFR therapy in genomically-selected patients using ctDNA. However, alternative mechanisms underpinning resistance beyond genomics -mainly related to the tumor microenvironment-have been unveiled, specifically relevant in patients receiving chemotherapy-based multi-drug treatment in first line. This review explores the complexity of the multifaceted mechanisms that mediate secondary resistance to anti-EGFR therapies and potential therapeutic strategies to circumvent acquired resistance.